2020
DOI: 10.1002/ardp.202000120
|View full text |Cite
|
Sign up to set email alerts
|

Natural indole‐containing alkaloids and their antibacterial activities

Abstract: As the growth in resistance to bacterial infection treatments poses a grave threat to global health in the 21st century, there is a constant need to explore novel antibacterial agents that have the ability to overcome drug resistance. Indole-containing alkaloids are widely distributed in nature, and a variety of indole-containing alkaloids have already been applied in clinical practice, proving that indole-containing alkaloids are fascinating and privileged scaffolds for the development of novel drugs. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 99 publications
1
36
0
Order By: Relevance
“…They are mainly distributed in Loganaceae, Apocynaceae, Rubiaceae Juss., and other plant groups. Based on their core structures, they are mainly divided into monomeric indole alkaloids, tryptamine indole alkaloids, monoterpenoid indole alkaloids, and bis-indolic alkaloids [ 8 , 12 ].…”
Section: Antibacterial Activity Of Different Types Of Natural Alkamentioning
confidence: 99%
See 2 more Smart Citations
“…They are mainly distributed in Loganaceae, Apocynaceae, Rubiaceae Juss., and other plant groups. Based on their core structures, they are mainly divided into monomeric indole alkaloids, tryptamine indole alkaloids, monoterpenoid indole alkaloids, and bis-indolic alkaloids [ 8 , 12 ].…”
Section: Antibacterial Activity Of Different Types Of Natural Alkamentioning
confidence: 99%
“…Berberine inhibits E. coli by negatively regulating the FtsZ protein [ 81 ]. Indole alkaloids can be used as potential drug resistance reversal agents that exert antibacterial activity by inhibiting FtsZ and MRSA pyruvate kinase [ 12 ].…”
Section: Antibacterial Mechanisms Of Natural Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indole derivatives with fascinating structural and mechanistic diversity are potential inhibitors of bacterial pyruvate kinase, GTPase, FtsZ, efflux pump, DNA gyrase, and topoisomerase IV, revealing the potential of indole derivatives for fighting against various bacteria, even hard‐to‐treat pathogens including MRSA. [ 47,48 ] Accordingly, 1,2,4‐triazole–indole hybrids are potential prototypes for the discovery of novel anti‐MRSA candidates.…”
Section: 24‐triazole–indole Hybridsmentioning
confidence: 99%
“…Indole (Figure 1) derivatives are ubiquitous in natural resources and they present a wide structural and mechanistic diversity. [9,10] Indole derivatives possess a variety of pharmacological properties, including anticancer, [11,12] antimalarial, [13,14] antiviral, [15,16] and antibacterial [17,18] activities, and play an intriguing role in the discovery of new drugs. The mechanistic study demonstrated that indole derivatives could exhibit the antibacterial activity through diverse mechanisms, including the inhibition of bacterial pyruvate kinase (PK), GTPase, filamentous temperature-sensitive protein Z (FtsZ), efflux pump, DNA gyrase, and topoisomerase IV; thus, these derivatives possess a potential activity against a panel of clinically important drug-sensitive and drug-resistant, and even multidrugresistant pathogens including MRSA.…”
mentioning
confidence: 99%